Hubungan Komitmen Kerja dan Kecerdasan Emosional dengan Prestasi Kerja Pegawai Akademi Keperawatan Kabupaten Kolaka - Evodius Nasus (Jurnal Surya Medika (JSM), 2019)
This study aimed to examine and analyze empirically the effect of working motivation, working commitment, and emotional intelligence on the working achievement of staff at Kolaka Government’s Academy of Nursing. The study was explanatory research which aimed at explaining the position of variables under investigation as well as the relationship between them and the effect of one variable on the others. Results showed that: (1) working motivation, working commitment, and emotional intelligence had a positively significant effect on the working achievement of staff at Kolaka Government’s Academy of Nursing; (2) working motivation had a positive significant effect on the working achievement of staff at Kolaka Government’s Academy of Nursing; (3) working commitment had a positively significant effect on the working achievement of staff at Kolaka Government’s Academy of Nursing; and (4) emotional intelligence had a positively significant effect on the working achievement of staff at Kolaka Government’s Academy of Nursing.